BORU NI RAJA HATOBAN "Tinjauan Filsafat Anthropologis atas Kaum Perempuan di dalam Budaya Batak Toba" - Simamora, Serpulus T (LOGOS, 2002)
One of many definitions offered to explain human existence is that humanbeing is a paradoxal being. By paradoxical being one intends that the veryexistence of human being is perceived in its seemingly contradictoryexpression without being contradiction. Human being is materialspiritual,individual-social, etc. This paradoxical nature constitutes humanexistence. It affects essentially his/her personality, religion, act, culture,etc. Social status of women in Toba Batak culture is placed in suchparadoxical situation too. In one hand, they are invoked as â€œBoru niRajaâ€ (the honored daughter), but on the other hand, they are treated asâ€œhatobanâ€ (slaves). This article seeks to show critically the place of TobaBatak women in Toba Batak culture. Our purpose, therefore, is to presentthe social status of Toba Batak women inherited culturally fromancestors. By critically we mean that we seek to present fairly the socialstatus of women in both its negative side and positive one.